The Impact Of Marketing Management On Customer Loyalty And Company Financial Performance: A Case Study On Retail Companies In Indonesia - Zainuddin, Muhammad Zabir; Mahrani, Sri Wiyati; Suprianto, Ghalib (SEAN Institute, 2024)
This research explores the impact of marketing management on customer loyalty and financial performance of retail companies in Indonesia. Using literature review and case study methods, this research analyzes various marketing strategies, particularly Customer Relationship Management (CRM), and their effects on customer satisfaction and loyalty as well as financial performance. The results show that effective implementation of CRM strategies can increase customer satisfaction and loyalty, which in turn has a positive impact on the company's financial performance. The case studies conducted show that a good CRM strategy can strengthen relationships with customers and maintain their loyalty. The conclusion of this study is that retail companies in Indonesia should focus on developing and implementing marketing strategies that focus on customer satisfaction and loyalty to achieve long-term success in a competitive industry.